2019
DOI: 10.3390/su11226318
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Urban Forests: Opportunities for Promoting the Wild Side of the Urban Green Infrastructure

Abstract: Many cities aim to increase urban forest cover to benefit residents through the provision of ecosystem services and to promote biodiversity. As a complement to traditional forest plantings, we address opportunities associated with “emerging urban forests” (i.e., spontaneously developing forests in cities) for urban biodiversity conservation. We quantified the area of successional forests and analyzed the species richness of native and alien plants and of invertebrates (carabid beetles, spiders) in emerging for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 172 publications
3
34
1
3
Order By: Relevance
“…In contrast, R. pseudoacacia impacts were not due to decreased light availability, but rather due to nitrogen fixation and increased soil nitrogen availability (Rice et al 2004), resulting in increasing alpha diversity or no impacts, similar to other studies (Sitzia et al 2012;Hejda et al 2017;Gentili et al 2019). However, still other studies revealed decreases of species diversity by R. pseudoacacia, in comparison with Betula pendula urban forests (Kowarik et al 2019), Q. cerris and Q. pubescens thermophilous forests (Lazzaro et al 2018) or shrublands on abandoned fields in China (Kou et al 2016). Therefore, although our results suggested increased alpha diversity in R. pseudoacacia forests, it can only be compared with mature native temperate forests in Europe, as comparisons with other reference ecosystems (see above) are in contrast.…”
Section: Discussioncontrasting
confidence: 55%
“…In contrast, R. pseudoacacia impacts were not due to decreased light availability, but rather due to nitrogen fixation and increased soil nitrogen availability (Rice et al 2004), resulting in increasing alpha diversity or no impacts, similar to other studies (Sitzia et al 2012;Hejda et al 2017;Gentili et al 2019). However, still other studies revealed decreases of species diversity by R. pseudoacacia, in comparison with Betula pendula urban forests (Kowarik et al 2019), Q. cerris and Q. pubescens thermophilous forests (Lazzaro et al 2018) or shrublands on abandoned fields in China (Kou et al 2016). Therefore, although our results suggested increased alpha diversity in R. pseudoacacia forests, it can only be compared with mature native temperate forests in Europe, as comparisons with other reference ecosystems (see above) are in contrast.…”
Section: Discussioncontrasting
confidence: 55%
“…This Special Issue covers a broad geographical range, with contributions from Africa [17], Asia [18][19][20], Australia [21,22], Europe [23][24][25][26][27][28][29][30] and North America [31][32][33]. It explores a range of ecosystems in the urban realm, spans natural remnants such as forests [30,32], wetlands [18,21], and natural grasslands [17,22], traditional urban greenspaces including cemeteries [33], gardens [29,31], and, finally, novel urban ecosystems such as green roofs and constructed wetlands [20,26], built-up areas [23], railway bridges [24] and emerging forests on vacant land [27]. In combination, a wide range of socio-cultural and environmental settings are explored and discussed.…”
Section: Geographical Range and Systems Addressedmentioning
confidence: 99%
“…Several papers explore biodiversity in relation to diverse features of urban environments and address a range of animal groups [21,24,27,31,33] and plants [17,18,20,22,27,30,32], including some multi-taxa studies [24,26,27]. Other papers explicitly address urban environments as socio-ecological systems [19,22,25], or further methodological approaches in understanding the people-nature intersection in cities [23,28,29].…”
Section: Geographical Range and Systems Addressedmentioning
confidence: 99%
“…Within the already established model ecosystem (i.e., grassland), the covered urbanization gradient can be extended toward more extreme settings in terms of aridity or spatial isolation (e.g., dry grassland on roof tops, road verges, and block courtyards); • The suite of model ecosystems can be expanded successively, e.g., with urban ponds to support analyses on the role of urbanization for aquatic biodiversity patterns. A further extension might cover emerging urban woodlands as a model system that allows insights into community assembly and ecosystem functioning in "wild" ecosystems that largely develop without direct human interferences in urban regions [148];…”
Section: Discussionmentioning
confidence: 99%